Now more than ever: building a resilient public health future through inclusive leadership - Magaña, Laura; Benjamin, Georges C. (Frontiers in Public Health, 2025)
This paper explores the urgent need for an inclusive model of leadership in public health, particularly in the context of accelerating social and political change. Drawing on lessons from the COVID-19 pandemic and other recent public health crises, the paper argues that traditional top-down leadership structures—often disconnected from the communities most impacted—are insufficient for responding to modern challenges. Instead, public health systems must invest in cultivating leaders who are embedded in, trusted by, and responsive to diverse populations. Citing workforce declines, public mistrust (1), and the harassment of health officials (2) before, during, and after the COVID-19 pandemic, this paper calls for a national leadership training agenda that spans the academic-to-practice continuum and emphasizes mentorship, flexible educational models, and integration with public health jurisdictions and community-based organizations. The paper also recommends reforming leadership metrics to prioritize measurable impact over positional authority. Ultimately, this paper positions adaptive, equity-focused leadership development as foundational to strengthening the nation’s public health infrastructure. It offers a forward-looking, inclusive vision that aligns leadership development with the evolving realities and demands of 21st-century public health.